2023
DOI: 10.5056/jnm22198
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux Characteristics in Supragastric Belching Patients With Positive Versus Negative pH Monitoring: An Evidence of Secondary Gastroesophageal Reflux Disease From Excessive Belching

Abstract: Background/AimsA high prevalence of GERD has been reported in patients with supragastric belching. We aim to evaluate reflux characteristics and explore the temporal relationship between supragastric belches (SGBs) and reflux episodes in GERD patients with excessive belching. MethodsTwenty-four hour esophageal pH-impedance monitoring was analyzed. Reflux episodes were classified into: refluxes preceded by SGBs, followed by SGBs, and lone refluxes. Reflux characteristics were compared between patients with pH-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(72 reference statements)
1
1
0
Order By: Relevance
“…This finding is consistent with a study by Kessing et al that showed patients with severe reflux symptoms had a greater frequency of supragastric belches [24]. If there is a causal relationship between reflux events and supragastric belching, using PPIs could help alleviate the behavioral response to the discomfort associated with acid exposure in the esophagus [25 ▪ ].…”
Section: Management Of Rumination Syndrome and Supragastric Belchingsupporting
confidence: 90%
“…This finding is consistent with a study by Kessing et al that showed patients with severe reflux symptoms had a greater frequency of supragastric belches [24]. If there is a causal relationship between reflux events and supragastric belching, using PPIs could help alleviate the behavioral response to the discomfort associated with acid exposure in the esophagus [25 ▪ ].…”
Section: Management Of Rumination Syndrome and Supragastric Belchingsupporting
confidence: 90%
“… 1 Belching correlates with supragastric or gastric belching. 1 - 5 However, recent studies have described patients who cannot belch due to failure of the upper esophageal sphincter (UES) to relax. 6 - 8 These patients complained of recurrent chest pain, abdominal bloating, discomfort, or nausea.…”
mentioning
confidence: 99%